Expressão da linguagem escrita por disléxicos adultos em processo seletivo - Sacchetto, Karen Kaufmann (2012)
The Developmental Dyslexia is known as a neuro-biological disturbance which main characteristic is in the difficulty in word recognition. The Developmental Dyslexia has been the subject of numerous studies involving from young children to teenagers with the intent to better advice teachers, parents and students of how to handle with their difficulties, by means of individualized strategies and adaptations allowing the adequate development of their respective competences. In Brazil the researches on adult dyslexia are considerably less developed compared to studies on children to teenagers. Objective: this study proposes to verify, by means of analysis of writing examinations required in the selective process for admission to university, the most frequent standards of errors and the auto-corrective strategies found in the written production of dyslexic adults. Method: the use of qualitative analysis, with quantitative content, it has been identified the number of errors committed in each handwritten expression found in the complete text written for the selection process for admission to the university for 6 adult dyslexic candidates. A complementary analysis resource was added with the submission of two questionnaires applied during individual interviews before and after the examination. Results: it has been found that most of the errors committed referred to complex rules (accentuation) followed by disturbances in the word segment structures, in agreement with the difficulties mentioned in the literature. Conclusion: the dyslexic candidates that arrive at the university level of learning present conditions to develop themselves provided they learn about their limitations and are encouraged to follow on in their accomplishments. At the same time the university level teaching institutions must establish conditions to face situations needed to comply with their legal and secured rights, and be available to allow to these future students to use the tools, strategies and adaptations to start, remain and finalize their university courses in equal conditions as their other colleagues.